2017
DOI: 10.2298/zmspn1733231s
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of macrofungi extracts on phytopathogenic fungal strains of genera Fusarium sp. and Alternaria sp.

Abstract: During the last decades, intensive application of synthetic fungicides in the agricultural crop protection practice caused growing concern for the existence of toxic chemical residues in food as well as in the whole environment. Instead of using synthetic fungicides, it is suggested that crop protection be carried out by using preparations based on compounds of natural origin (secondary metabolites of plants or microorganisms, including macrofungi from Basidiomycota) as biological control age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Additionally, water extracts from spent mushroom substrates of L. edodes suppressed mycelial growth of the rice blast fungus Pyricularia oryzae [ 40 ]. In addition, ethanolic extracts of Hydnum repandum , a mycorrhizal species commonly known as the sweet tooth or hedgehog mushroom and broadly distributed in Europe and Asia, had strong antifungal effects on various Fusarium species, including F. verticillioides [ 41 ]. Nonetheless, to date, there are no previous studies that showed inhibition of F. verticillioides by extracts from A. subrufescens , L. edodes , or P. ostreatus [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, water extracts from spent mushroom substrates of L. edodes suppressed mycelial growth of the rice blast fungus Pyricularia oryzae [ 40 ]. In addition, ethanolic extracts of Hydnum repandum , a mycorrhizal species commonly known as the sweet tooth or hedgehog mushroom and broadly distributed in Europe and Asia, had strong antifungal effects on various Fusarium species, including F. verticillioides [ 41 ]. Nonetheless, to date, there are no previous studies that showed inhibition of F. verticillioides by extracts from A. subrufescens , L. edodes , or P. ostreatus [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…More than 80 % are edible mushrooms, since their extracts might be generally be recognized as safe for use. As an example, ethanolic extracts of Hydnum repandum, a mycorrhizal species commonly known as the sweet tooth or hedgehog mushroom and broadly distributed in Europe and Asia, had strong antifungal effects on various Fusarium species (Spremo et al, 2017).…”
Section: Antifungal Compounds From Mushroom For-ming Fungi Active Against Mycotoxigenic Fungi In Cerealsmentioning
confidence: 99%
“…Phenolic acids are the main phenolic compounds in mushroom forming fungi that are proposed to be used as an easily accessible source of natural antioxidants (Nowacka et al, 2014). Recently, ethanolic extracts, known to be rich in phenolic compounds, from fruiting bodies of Hydnum repandum, and methanolic extracts of Stereum subtomentosum and Bjerkandera adusta, showed antifungal effects on F. verticillioides, F. pro liferatum and F. graminearum (Spremo et al, 2017). Phenolic acids have been measured in various species, but depending on the analytical methods used, not all the phenolic acids had been searched in all the studied mushrooms.…”
Section: Bioactive Proteins From Mushroom Forming Fungi With Activity Against Mycotoxigenic Speciesmentioning
confidence: 99%